Skip to content
Related Articles

Related Articles

Improve Article

Class 12 RD Sharma Solutions – Chapter 11 Differentiation – Exercise 11.3 | Set 1

  • Last Updated : 08 May, 2021
Geek Week

Question 1. Differentiatey=cos^{-1}(2x\sqrt{1-x^2})  , 1/√2 < x < 1 with respect to x.

Solution:

We have,

y=cos^{-1}(2x\sqrt{1-x^2})  , 1/√2 < x < 1.

On putting x = cos θ, we get,

y =cos^{-1}(2cosθ\sqrt{1-cos^2θ})



=cos^{-1}(2cosθ\sqrt{sin^2θ})

= cos−1(2cos θ sin θ)

= cos−1(sin 2θ)

=cos^{-1}(cos(\frac{π}{2}-2θ))

Now, 1/√2 < x < 1

=> 1/√2 < cos θ < 1

=> 0 < θ < π/4

=> 0 < 2θ < π/2



=> 0 > −2θ > −π/2

=> π/2 > (π/2−2θ) > 0

So, y =\frac{π}{2}-2cos^{-1}x

Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(\frac{π}{2}-2cos^{-1}x)

=0-2\left(\frac{-1}{\sqrt{1-x^2}}\right)

=\frac{2}{\sqrt{1-x^2}}

Question 2. Differentiatey=cos^{-1}\left(\sqrt{\frac{1+x}{2}}\right)  ,−1 < x < 1 with respect to x.

Solution:

We have,y=cos^{-1}\left(\sqrt{\frac{1+x}{2}}\right)  ,−1 < x < 1.

On putting x = cos 2θ, we get,



y =cos^{-1}\left(\sqrt{\frac{1+cos2θ}{2}}\right)

=cos^{-1}\left(\sqrt{\frac{2cos^2θ}{2}}\right)

=cos^{-1}\left(\sqrt{cos^2θ}\right)

=cos^{-1}\left(cosθ\right)

Now, −1 < x < 1

=> −1 < cos 2θ < 1

=> 0 < 2θ < π

=> 0 < θ < π/2

So, y =\frac{1}{2}cos^{-1}x

Differentiating with respect to x, we get,



\frac{dy}{dx}=\frac{d}{dx}(\frac{1}{2}cos^{-1}x)

=\frac{-1}{2\sqrt{1-x^2}}

Question 3. Differentiatey=sin^{-1}\left(\sqrt{\frac{1-x}{2}}\right)  , 0 < x < 1 with respect to x.

Solution:

We have,y=sin^{-1}\left(\sqrt{\frac{1-x}{2}}\right)  , 0 < x < 1.

On putting x = cos 2θ, we get,

y =sin^{-1}\left(\sqrt{\frac{1-cos2θ}{2}}\right)

=sin^{-1}\left(\sqrt{\frac{2sin^2θ}{2}}\right)

=sin^{-1}\left(sinθ\right)

Now, 0 < x < 1

=> 0 < cos 2θ < 1



=> 0 < 2θ < π/2

=> 0 < θ < π/4

So,y = \frac{1}{2}cos^{-1}x

Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(\frac{1}{2}cos^{-1}x)

=\frac{-1}{2\sqrt{1-x^2}}

Question 4. Differentiatey=sin^{-1}(\sqrt{1-x^2})  , 0 < x < 1 with respect to x.

Solution:

We have,y=sin^{-1}(\sqrt{1-x^2})  , 0 < x < 1

On putting x = cos θ, we get,

y =sin^{-1}(\sqrt{1-cos^2θ})



=sin^{-1}(\sqrt{sin^2θ})

=sin^{-1}\left(sinθ\right)

Now, 0 < x < 1

=> 0 < cos θ < 1

=> 0 < θ < π/2

So, y = cos−1x

Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(cos^{-1}x)

=\frac{-1}{\sqrt{1-x^2}}

Question 5. Differentiatey=tan^{-1}\left(\frac{x}{\sqrt{a^2-x^2}}\right)  , −a < x < a with respect to x.

Solution:

We have,y=tan^{-1}\left(\frac{x}{\sqrt{a^2-x^2}}\right)  , −a < x < a

On putting x = a sin θ, we get,

y =tan^{-1}\left(\frac{asinθ}{\sqrt{a^2-a^2sin^2θ}}\right)

=tan^{-1}\left(\frac{asinθ}{\sqrt{a^2cos^2θ}}\right)

=tan^{-1}\left(\frac{asinθ}{acosθ}\right)

=tan^{-1}\left(tanθ\right)

Now, −a < x < a

=> −1 < x/a < 1

=> −π/2 < θ < π/2

So,y=sin^{-1}(\frac{x}{a})



Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(sin^{-1}\frac{x}{a})

=\frac{1}{a\sqrt{1-\frac{x^2}{a^2}}}

=\frac{a}{a\sqrt{a^2-x^2}}

=\frac{1}{\sqrt{a^2-x^2}}

Question 6. Differentiatey=sin^{-1}\left(\frac{x}{\sqrt{a^2+x^2}}\right)  with respect to x.

Solution:

We have,y=sin^{-1}\left(\frac{x}{\sqrt{a^2+x^2}}\right)

On putting x = a tan θ, we get,

y =sin^{-1}\left(\frac{atanθ}{\sqrt{a^2+a^2tan^2θ}}\right)

=sin^{-1}\left(\frac{atanθ}{\sqrt{a^2sec^2θ}}\right)



=sin^{-1}\left(\frac{atanθ}{asecθ}\right)

=sin^{-1}(sinθ)

= θ

=tan^{-1}(\frac{x}{a})

Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(tan^{-1}(\frac{x}{a}))

=\frac{1}{a(1+\frac{x^2}{a^2})}

=\frac{a^2}{a(a^2+x^2)}

=\frac{a}{\sqrt{a^2+x^2}}

Question 7. Differentiatey=sin^{-1}\left(2x^2-1\right)  , 0 < x < 1 with respect to x.

Solution:



We have,y=sin^{-1}\left(2x^2-1\right)  , 0 < x < 1

On putting x = cos θ, we get,

y =sin^{-1}\left(2cos^2θ-1\right)

=sin^{-1}\left(cos2θ\right)

=sin^{-1}\left(sin(\frac{π}{2}-2θ)\right)

Now, 0 < x < 1

=> 0 < cos θ < 1

=> 0 < θ < π/2

=> 0 < 2θ < π

=> π/2 > (π/2−2θ) > −π/2

So, y =\frac{π}{2}-2cos^{-1}x

Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(\frac{π}{2}-2cos^{-1}x)

=0-2\left(\frac{-1}{\sqrt{1-x^2}}\right)

=\frac{2}{\sqrt{1-x^2}}

Question 8. Differentiatey=sin^{-1}\left(1-2x^2\right)  , 0 < x < 1 with respect to x.

Solution:

We havey=sin^{-1}\left(1-2x^2\right)  , 0 < x < 1

On putting x = sin θ, we get,

y =sin^{-1}\left(1-2sin^2θ\right)

=sin^{-1}\left(cos2θ\right)



=sin^{-1}\left(sin(\frac{π}{2}-2θ)\right)

Now, 0 < x < 1

=> 0 < sin θ < 1

=> 0 < θ < π/2

=> 0 < 2θ < π

=> π/2 > (π/2−2θ) > −π/2

So, y =\frac{π}{2}-2sin^{-1}x

Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(\frac{π}{2}-2sin^{-1}x)

=0-2\left(\frac{1}{\sqrt{1-x^2}}\right)

=\frac{-2}{\sqrt{1-x^2}}

Question 9. Differentiatey=cos^{-1}\left(\frac{x}{\sqrt{a^2+x^2}}\right)  with respect to x.

Solution:

We have,y=cos^{-1}\left(\frac{x}{\sqrt{a^2+x^2}}\right)

Putting x = cot θ, we get,

y =cos^{-1}\left(\frac{acotθ}{\sqrt{a^2+a^2cot^2θ}}\right)

=cos^{-1}\left(\frac{acotθ}{\sqrt{a^2cosec^2θ}}\right)

=cos^{-1}\left(\frac{acotθ}{acosecθ}\right)

=cos^{-1}(cosθ)

= θ

=cot^{-1}(\frac{x}{a})



Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(cot^{-1}(\frac{x}{a}))

=\frac{-1}{a(1+\frac{x^2}{a^2})}

=\frac{-a^2}{a(a^2+x^2)}

=\frac{-a}{\sqrt{a^2+x^2}}

Question 10. Differentiatey=sin^{-1}\left(\frac{sinx+cosx}{\sqrt{2}}\right)  , −3π/4 < x < π/4 with respect to x.

Solution:

We have,y=sin^{-1}\left(\frac{sinx+cosx}{\sqrt{2}}\right)  , −3π/4 < x < π/4

=sin^{-1}\left(sinx(\frac{1}{\sqrt{2}})+cosx(\frac{1}{\sqrt{2}})\right)

=sin^{-1}\left(sin(x+\frac{π}{4})\right)

Now, −3π/4 < x < π/4

=> −π/2 < (x+π/4) < π/2

So, y =x+\frac{π}{4}

Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(x+\frac{π}{4})

= 1 + 0

= 1

Question 11. Differentiatey=cos^{-1}\left(\frac{sinx+cosx}{\sqrt{2}}\right)  , −π/4 < x < π/4 with respect to x.

Solution:

We have,y=cos^{-1}\left(\frac{sinx+cosx}{\sqrt{2}}\right)  , −π/4 < x < π/4

=cos^{-1}\left(sinx(\frac{1}{\sqrt{2}})+cosx(\frac{1}{\sqrt{2}})\right)

=cos^{-1}\left(cos(x-\frac{π}{4})\right)



Now, −π/4 < x < π/4

=> −π/2 < (x−π/4) < 0

So, y =-(x-\frac{π}{4})

=-x+\frac{π}{4}

Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(-x+\frac{π}{4})

= −1 + 0

= −1

Question 12. Differentiatey=tan^{-1}\left(\frac{x}{1+\sqrt{1-x^2}}\right)  , −1 < x < 1 with respect to x.

Solution:

We have,y=tan^{-1}\left(\frac{x}{1+\sqrt{1-x^2}}\right)  , −1 < x < 1

On putting x = sin θ, we get,

y =tan^{-1}\left(\frac{sinθ}{1+\sqrt{1-sin^2θ}}\right)

=tan^{-1}\left(\frac{sinθ}{1+cosθ}\right)

=tan^{-1}\left(\frac{2sin\frac{θ}{2}cos\frac{θ}{2}}{2cos^2\frac{θ}{2}}\right)

=tan^{-1}\left(tan\frac{θ}{2}\right)

Now, −1 < x < 1

=> −1 < sin θ < 1

=> −π/2 < θ < π/2

=> −π/4 < θ/2 < π/4

So, y =\frac{1}{2}sin^{-1}x

Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(\frac{1}{2}sin^{-1}x)

=\frac{1}{2\sqrt{1-x^2}}

Question 13. Differentiatey=tan^{-1}\left(\frac{x}{a+\sqrt{a^2-x^2}}\right)  , −a < x < a with respect to x.

Solution:

We have,y=tan^{-1}\left(\frac{x}{a+\sqrt{a^2-x^2}}\right)  , −a < x < a

On putting x = a sin θ, we get,

=tan^{-1}\left(\frac{asinθ}{a+\sqrt{a^2-a^2sin^2θ}}\right)

=tan^{-1}\left(\frac{asinθ}{a(1+cosθ)}\right)

=tan^{-1}\left(\frac{2sin\frac{θ}{2}cos\frac{θ}{2}}{2cos^2\frac{θ}{2}}\right)

=tan^{-1}\left(tan\frac{θ}{2}\right)



Now, −a < x < a

=> −1 < x/a < 1

=> −π/2 < θ < π/2

=> −π/4 < θ/2 < π/4

So, y =\frac{1}{2}sin^{-1}(\frac{x}{a})

Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(\frac{1}{2}sin^{-1}(\frac{x}{a}))

=\frac{1}{2a\sqrt{1-\frac{x^2}{a^2}}}

=\frac{a}{2a\sqrt{a^2-x^2}}

=\frac{1}{2\sqrt{a^2-x^2}}

Question 14. Differentiatey=sin^{-1}\left(\frac{x+\sqrt{1-x^2}}{\sqrt{2}}\right)  , −1 < x < 1 with respect to x.

Solution:

We have,y=sin^{-1}\left(\frac{x+\sqrt{1-x^2}}{\sqrt{2}}\right)  , −1 < x < 1

On putting x = sin θ, we get,

y=sin^{-1}\left(\frac{sinθ+\sqrt{1-sin^2θ}}{\sqrt{2}}\right)

=sin^{-1}\left(\frac{sinθ+cosθ}{\sqrt{2}}\right)

=sin^{-1}\left(sin(θ+\frac{π}{4})\right)

Now, −1 < x < 1

=> −1 < sin θ < 1

=> −π/2 < θ < π/2

=> −π/2 < (θ+π/4) < 3π/4

So, y =sin^{-1}x+\frac{π}{4}

Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(sin^{-1}x+\frac{π}{4})

=\frac{1}{\sqrt{1-x^2}}+0

=\frac{1}{\sqrt{1-x^2}}

Question 15. Differentiatey=cos^{-1}\left(\frac{x+\sqrt{1-x^2}}{\sqrt{2}}\right)  , −1 < x < 1 with respect to x.

Solution:

We have,y=cos^{-1}\left(\frac{x+\sqrt{1-x^2}}{\sqrt{2}}\right)  , −1 < x < 1

On putting x = sin θ, we get,

y=cos^{-1}\left(\frac{sinθ+\sqrt{1-sin^2θ}}{\sqrt{2}}\right)

=cos^{-1}\left(\frac{sinθ+cosθ}{\sqrt{2}}\right)



=cos^{-1}\left(cos(θ-\frac{π}{4})\right)

Now, −1 < x < 1

=> −1 < sin θ < 1

=> −π/2 < θ < π/2

=> −3π/4 < (θ−π/4) < π/4

So, y =-(sin^{-1}x-\frac{π}{4})

=-sin^{-1}x+\frac{π}{4}

Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(-sin^{-1}x+\frac{π}{4})

=\frac{-1}{\sqrt{1-x^2}}+0

=\frac{-1}{\sqrt{1-x^2}}

Question 16. Differentiatey=tan^{-1}\left(\frac{4x}{1-4x^{2}}\right)  , −1/2 < x < 1/2 with respect to x.

Solution:

We have,y=tan^{-1}\left(\frac{4x}{1-4x^{2}}\right)  , −1/2 < x < 1/2

On putting 2x = tan θ, we get,

y=tan^{-1}\left(\frac{2tanθ}{1-tan^2θ}\right)

=tan^{-1}\left(tan2θ\right)

Now, −1/2 < x < 1/2

=> −1 < 2x < 1

=> −1 < tan θ < 1

=> −π/4 < θ < π/4

=> −π/2 < 2θ < π/2

Therefore, y = 2 tan−1 (2x)

Differentiating with respect to x, we get,

\frac{dy}{dx}=\frac{d}{dx}(2 tan^{−1}(2x))

=\frac{4}{\sqrt{1+(2x)^2}}

=\frac{4}{\sqrt{1+4x^2}}

Attention reader! All those who say programming isn’t for kids, just haven’t met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12. 

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.




My Personal Notes arrow_drop_up
Recommended Articles
Page :